MODERASI MODAL PSIKOLOGIS PADA PENGARUH WORK FAMILY CONFLICT TERHADAP BURNOUT - Rio Pramono Jati; Ririn Handayani; Adolf Bastian; Didik Siswanto (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
This study aims to analyze the effect of work-family conflict on burnout with psychological capital as a moderating variable. The population of this study consisted of 171 employees of the Representative Office of the Audit Board of the Republic of Indonesia (BPK RI) in Riau. The sample used was 118 respondents, determined based on the Krejcie and Morgan (1970) table. The verification analysis technique in this study was conducted using Structural Equation Modelling (SEM) and Partial Least Square (PLS) as analytical tools. The results of the study indicate that work-family conflict has a positive and significant effect on burnout among BPK RI auditors, implying that the higher the conflict between work and family demands, the higher the level of emotional exhaustion, apathy toward work, and decline in auditors’ work productivity. Furthermore, psychological capital was proven to significantly and negatively moderate the effect of work-family conflict on burnout, indicating that auditors with higher levels of psychological capital tend to be more capable of maintaining mental resilience and emotional stability, while also reducing the negative impact of work-family conflict on the emergence of burnout.